A novel non-thermal resection tool in endoscopic management of scarred polyps - Kesavan Kandiah; Sharmila Subramaniam; Fergus Chedgy; Sreedhari Thayalasekaran; Daniel Venetz; Patrick Aepli; Pradeep Bhandari (Endoscopy International Open, 2019)
Background and study aims Scarred polyps are challenging to resect using conventional endoscopic mucosal resection (EMR) techniques. The aim of this pilot study was to assess the feasibility of the EndoRotor device in resecting scarred polyps arising from previous endoscopic resection attempts. Patients and methods This was a prospective pilot study of patients with scarred colonic polyps treated using EndoRotor carried out in two centers. Results A total of 19 patients were included in this study. The overall cure rate using EndoRotor was 84 %; 10 patients (52.6 %) achieved cure after one attempt and six patients (31.5 %) achieved cure after two attempts. A total of three patients who had polyp recurrence after the first EndoRotor resection were referred for either endoscopic submucosal dissection (2 patients) or surgery (1 patient) due to difficult access. There were no perforations, delayed bleeding, post-polypectomy syndrome or complications requiring surgery. Conclusions In this pilot study, the novel non-thermal device (EndoRotor) has been demonstrated to be a safe and effective technique in challenging management of scarred polyps. Further randomized controlled trials comparing this technique with APC, hot avulsion, ESD and endoscopic full-thickness resection are required to ascertain the utility of EndoRotor in the hands of non-expert endoscopists.